RETRACTED: The Influence of Organizational Culture, Physical Work Environment and Compensation (Reward) on Employee Performance at PT. Adroady Jakarta - Ahmad Diky Alfarisi; Resti Hardini; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to determine the effect of, Organizational Culture,Physical Work Environment and Compensation (Reward) on Employee Performance at PT. Adroady, Jakarta. The data of this study used primary data in the form of questionnaires to 158 employees of PT. Adroady, Jakarta. Data analysis techniques using multiple linear regression analysis and using the SPSS program. The results showed an influence between Organizational Culture (X1), Employee Performance (Y) of 0.351 and an influence of 35,1%. Similarly, the variable Physical Work Environment (X2) on Employee Performance (Y) of 0.233 and has an influence of 23.3%. Then for the variable Compensation (Reward) (X3) on Employee Performance (Y) of 0.199 and has an influence of 19,9%. Partially or simultaneously have a strong influence among the three variables, the most significant is the Organizational Culture variable of 0,000. The results of this research hope that companies can increase compensation (Rewards) which can support employee performance.